2007
DOI: 10.1186/1750-2187-2-7
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of TRAIL-resistant LNCaP cells by resveratrol (3, 4', 5 tri-hydroxystilbene): molecular mechanisms and therapeutic potential

Abstract: Background: We have previously shown that prostate cancer LNCaP cells are resistant to TRAIL, and downregulation of PI-3K/Akt pathway by molecular and pharmacological means sensitizes cells to undergo apoptosis by TRAIL and curcumin. The purpose of this study was to examine the molecular mechanisms by which resveratrol sensitized TRAIL-resistant LNCaP cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 68 publications
4
70
0
Order By: Relevance
“…However, some tumour cells are resistant to TRAIL-mediated cytotoxicity (19). Previously we and others have demonstrated that the LNCaP cell line is resistant to TRAIL-induced apoptosis (7,10,11,13,14,16,31,35,40). The recombinant human TRAIL used in this study is a soluble protein based on a natural ligand (13,34).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, some tumour cells are resistant to TRAIL-mediated cytotoxicity (19). Previously we and others have demonstrated that the LNCaP cell line is resistant to TRAIL-induced apoptosis (7,10,11,13,14,16,31,35,40). The recombinant human TRAIL used in this study is a soluble protein based on a natural ligand (13,34).…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated apoptotic pathways are significant in the initiation and progression of prostate cancer (4,7,17,39). The data accumulated from in vitro and in vivo studies suggest that TRAIL plays an important role in the maintenance of immune homeostasis, host tumour surveillance and defence against cancer cells (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations